A Study of Investors’ Attitude towards Mutual fund in Kathmandu City, Nepal - Bajracharya, Rajan Bilas (Journal of Advanced Academic Research, 2018)
Mutual fund is an investment tool which assembles the savings of millions of small investors into huge capital formation. The primary goal behind investment in mutual fund is to earn goods return with comparatively low risk. The main purpose of doing this research is to find out a relationship between selected demographic and socioeconomic characteristics and investors’ attitude towards mutual. Another purpose of this research was to rank different sources investors use to make investment decision on the basis on their preference. By using Likert scale (0 to 1) and three levels (positive, neutral, negative) in structured questionnaire, researchers have measured the level of attitude towards mutual fund and levels of preference of sources are to investment decision. It is found that, the investors attitude is not independent towards mutual fund on the basis of demographic and socio economic variable (age, gender, monthly income, investment level, educational qualification). Also, among selected sources, investors provide their highest preference to Brokers/Agents to make investment. The study has suggested some important policy measures such as regulatory change, creating investors awareness, encouraging the private companies to raise fund through mutual fund.